Effects of Coarse and Fine Crushed Clay Brick Content on the Compressive Strength of Recycled Aggregate Concrete and the Microscopic Mechanism - Jin Chang; Shi-lin Luo; Aierken Ailifeila; Lin-lin Chong; Jian-qing Jiang (Geofluids)
The objective of this study is to investigate the compressive strength and microstructural evolution of recycled aggregate concrete (RAC) containing coarse and fine clay brick aggregates. The compressive strength tests, scanning electron microscopy (SEM) observations, and X-ray diffraction (XRD) tests were performed on RAC and natural aggregate concrete (NAC) containing different coarse and fine crushed clay brick contents. The results showed that the compressive strength of NAC and RAC decreased with the increase of crushed clay brick content, and the growth rate of their compressive strength slowed down with the increase of age. At the same age and replacement rate, fine crushed clay bricks had less effect on the compressive strength of RAC than coarsely crushed clay bricks. The compressive strength of RAC aged 60 days, mixed with 60% fine brick slag and mixed with 60% coarse brick slag, is 10.49% and 14.75% lower than that of RAC aged 60 days and mixed with 0% fine brick slag, respectively. Compared with RAC, the compressive strength of NAC was more significantly affected by grading. The interfacial transition zones inside RAC had loose crystals and high porosity, with a weak adhesion between the crushed clay bricks and mortar interfaces. The crushed clay bricks did not affect the types of concrete hydration products, and Calcium-Silicate-Hydrate (C-S-H) and Ca(OH)2 crystals remained the early hydration products in RAC with crushed clay bricks. Nevertheless, the crushed clay bricks inhibited the hydration reaction of the concrete, resulting in decreasing hydration products in NAC, RAC, and RAC with crushed clay bricks.